2007
DOI: 10.1002/jcb.21260
|View full text |Cite
|
Sign up to set email alerts
|

Role of phospholipase D2 in anti‐apoptotic signaling through increased expressions of Bcl‐2 and Bcl‐xL

Abstract: We have previously reported that Fas-resistant A20 cells (FasR) have phospholipase D (PLD) activity upregulated by endogenous PLD2 overexpression. In the present study, we investigated how overexpressed PLD2 in FasR could generate survival signals by regulating the protein levels of anti-apoptotic Bcl-2 and Bcl-xL. To confirm the effect of PLD2 on Bcl-2 protein levels, we transfected PLD2 into wild-type murine B lymphoma A20 cells. The transfected cells showed markedly the increases in Bcl-2 and Bcl-xL protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 44 publications
1
18
1
Order By: Relevance
“…Recently, the function of DPPA in the regulation of pathological changes has begun to be clarified. Recently reports indicated that DPPA plays a critical role in regulating Bcl‐2 expression in a cell type‐dependent manner 8, 9. In addition, DPPA reportedly inhibits renal interstitial fibrosis in a rat diabetic nephropathy model 10.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, the function of DPPA in the regulation of pathological changes has begun to be clarified. Recently reports indicated that DPPA plays a critical role in regulating Bcl‐2 expression in a cell type‐dependent manner 8, 9. In addition, DPPA reportedly inhibits renal interstitial fibrosis in a rat diabetic nephropathy model 10.…”
Section: Introductionmentioning
confidence: 98%
“…In contrast, PLD2 has a constitutively high activity in the presence of PI4,5P 2 and is insensitive to PLD1 activators (28,32). PLD2 has been implicated in various cellular events, such as antiapoptosis (38), endocytic recycling (39), endocytosis (40), differentiation of PC12 cells (41), actin-based membrane dynamics (42), and L1-dependent neurite outgrowth (43). Conclusions about some of these PLD functions are based on observations from experiments using primary alcohols, such as ethanol (EtOH) and 1-butanol.…”
mentioning
confidence: 99%
“…In response to Fas, PLD has been reported to prevent apoptosis by generating PA and increasing Bcl-2 and Bcl-xL expression. 31 In response to the mitochondrial apoptotic signal, PLD is known to prevent apoptosis due to the elevation of PA levels and the subsequent decrease in the expression of tumor suppressor genes such as Egr-1 and PTEN.…”
Section: Discussionmentioning
confidence: 99%